SPECIFICS OF GROUNDWATER FLOW FORMATION IN THE UPPER STREAMS BASIN OF THE SOTK RIVER AND ITS CONTAMINATION POSSIBILITIES FROM OPERATION OF SOTK GOLD MINE (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Mining of Sotk gold deposit is a potential threat to groundwater contamination of the Masrik basin and Lake Sevan. The article presents geologicalhydrogeological specifics of formation, transit and discharge of groundwater in the upper streams of the Sotk River. According to studies, the river's recharge from groundwater is related to drainage waters occurring in eluvial-deluvial sediments. Deeper ground water flow occurs under riverbed, in alluvial-proluvial sediments. Hydrogeological assessment has shown that the velocity and flow rate of groundwater flow are too small and do not contribute to the transport of contaminants through groundwater in considerable amounts.
Keywords: Sotk River Basin; groundwater recharge; contamination; transport of contaminants